Menemukan Makna Komunikasi di Era Teknologi: Perspektif Teori Heidegger, Logos, dan Kebenaran - Kaunang , Rezha Ribka (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Heidegger's thinking about Logos and truth shifts the focus from the traditional static view to a more dynamic and processual view. By emphasizing the role of language in revealing truth, Heidegger provides a new perspective on how we understand and experience reality. The aim of this research is to describe in detail how to find the meaning of communication in the technological era as viewed from the perspective of Heidegger's Theory, Logos and Truth. This research method applies Systematic Literature Review (SLR) using PRISMA guidelines. The research results show that Heidegger's logos theory provides a critical view of modern communication phenomena, especially in the context of social media, online news and instant communication. Logos, which Heidegger understood as the basis of human understanding and rationality, risks being reduced to a mere technical tool in the digital environment. Communication that occurs on these platforms often loses depth and nuance, replaced by information fragmentation and algorithmic interests that prioritize hype and user engagement over truth and deep understanding.